2016
DOI: 10.1681/asn.2015080903
|View full text |Cite
|
Sign up to set email alerts
|

EGF Receptor Inhibition by Erlotinib Increases Aquaporin 2–Mediated Renal Water Reabsorption

Abstract: Nephrogenic diabetes insipidus (NDI) is caused by impairment of vasopressin (VP) receptor type 2 signaling. Because potential therapies for NDI that target the canonical VP/cAMP/protein kinase A pathway have so far proven ineffective, alternative strategies for modulating aquaporin 2 (AQP2) trafficking have been sought. Successful identification of compounds by our high-throughput chemical screening assay prompted us to determine whether EGF receptor (EGFR) inhibitors stimulate AQP2 trafficking and reduce urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 85 publications
3
45
0
Order By: Relevance
“…AQP2 membrane trafficking can also be facilitated by other receptor ligands, including angiotensin, prostaglandin, and calcitonin (Jensen et al 2009(Jensen et al , 2010Li et al 2009;Bouley et al 2011), which affect the cAMP/PKA signalling pathway. In addition, we found that epidermal growth factor receptor (EGFR) inhibition can induce AQP2 phosphorylation in a similar pattern to VP, but independently of cAMP and PKA, suggesting a crosstalk between EGFR and VP signalling in AQP2 regulation (Cheung et al 2016). One possible common denominator in this crosstalk is Src (pp60 c-SRC ).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…AQP2 membrane trafficking can also be facilitated by other receptor ligands, including angiotensin, prostaglandin, and calcitonin (Jensen et al 2009(Jensen et al , 2010Li et al 2009;Bouley et al 2011), which affect the cAMP/PKA signalling pathway. In addition, we found that epidermal growth factor receptor (EGFR) inhibition can induce AQP2 phosphorylation in a similar pattern to VP, but independently of cAMP and PKA, suggesting a crosstalk between EGFR and VP signalling in AQP2 regulation (Cheung et al 2016). One possible common denominator in this crosstalk is Src (pp60 c-SRC ).…”
Section: Introductionmentioning
confidence: 85%
“…, ; Cheung et al . ). After 5 washes in PBS, tissues were cryoprotected in PBS, 30% sucrose overnight before being embedded in Tissue‐Tek O.C.T.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Although the disease is better understood and complications are less often seen currently due to our increased understanding of their causes, the necessity for frequent and high-volume urination is still a problem for survival and quality of life. There are several chemicals, including erlotinib, sildenafil, and simvastatin, that have been reported to activate urine-concentrating ability through nonvasopressin pathways in vivo and in vitro (710), but none of these studies showed complete restoration of urine-concentrating ability.…”
Section: Introductionmentioning
confidence: 99%